Political Communication of Election Legislative Candidates (Affirmative Action Analysis) Quota of 30 Percent of Women's Representation in the Legislative Election in the Election City of Pekalongan City - Dwirainaningsih, Yustiana Dwi (Law Research Review Quarterly, 2018)
Political communication is a political process which in this context is a political candidate for women who nominate themselves as candidates for parliament, the election law indirectly is one form of political accommodation on the demand for the importance of gender equality for women in the political sphere, while providing more big space political participation from women. Affirmative Action Policy with the first quota system carried out in the Election of Legislative assembly, Regional Representative Council and Regional People's Representative Council. This research is in order to obtain, process and conclude data and resolve a problem, therefore the author in this case uses sociological juridical legal research in the form of legal aspects based on the rules of law on political communication. In this case the researcher uses a problem approach, namely the qualitative descriptive method is a method that can raise facts, conditions, variables and phenomena that occur. In the future more and more women will take part and participate in the political arena, giving enlightenment, awareness and encouragement to women so that in various political activities such as participating in campaigns, voters, becoming legislative candidates, as well as legislators.